Multi-Hazard Groundwater Risks to the Drinking Water Supply in Bangladesh : Challenges to Achieving the Sustainable Development Goals - Shamsudduha, Mohammad; Joseph, George; Haque, Sabrina S.; Khan, Mahfuzur R.; Zahid, Anwar; Ahmed, Kazi Matin U. (World Bank, Washington, DC, 2019)
Groundwater currently provides 98 percent of all the drinking water supply in Bangladesh. Groundwater is found throughout Bangladesh but its quality (that is, arsenic and salinity contamination) and quantity (that is, water storage depletion) vary across hydrological environments, posing unique challenges to certain geographical areas and population groups. Yet, no national-scale, multi-hazard groundwater risk maps currently exist enabling water resource managers and policy makers to identify areas that are vulnerable to public health. This paper develops, for the first time, groundwater risk maps at the national scale for Bangladesh that combine information on arsenic, salinity, and water storage, using geospatial techniques, linking hydrological indicators for water quality and quantity to construct risk maps. A range of socioeconomic variables, including access to drinking and irrigation water supplies and social vulnerability (that is, poverty), are overlaid on these risk maps to estimate exposures. The multi-hazard groundwater risk maps show that a considerable proportion of land area (5 to 24 percent under extremely high to high risks) in Bangladesh is currently under combined risk of arsenic and salinity contamination, and groundwater storage depletion. As few as 6.5 million (2.2 million poor) to 24.4 million (8.6 million poor) people are exposed to a combined risk of high arsenic, salinity, and groundwater storage depletion. The multi-hazard groundwater risk maps reveal areas and exposure of population groups to water risks posed by arsenic and salinity contamination and depletion of water storage.